2021
DOI: 10.3389/fgene.2021.654517
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Key Genes Associated With the Process of Hepatitis B Inflammation and Cancer Transformation by Integrated Bioinformatics Analysis

Abstract: BackgroundHepatocellular carcinoma (HCC) has become the main cause of cancer death worldwide. More than half of hepatocellular carcinoma developed from hepatitis B virus infection (HBV). The purpose of this study is to find the key genes in the transformation process of liver inflammation and cancer and to inhibit the development of chronic inflammation and the transformation from disease to cancer.MethodsTwo groups of GEO data (including normal/HBV and HBV/HBV-HCC) were selected for differential expression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 95 publications
0
12
0
Order By: Relevance
“…Moreover, the SNHG16/miR-30a/RRM2 axis also accelerates BRCA cell proliferation and invasion, while miR-4500 could downregulate RRM2 and inhibit BRCA cell proliferation, invasion, and migration via suppressing the MAPK signaling pathway [ 38 , 39 ]. Moreover, RRM2 has been included in several bioinformatic-based clinical prognostic models [ 40 , 41 ]. In addition, a single gene bioinformatics study and one clinical pathology research study indicated that RRM2 expression could help in evaluating the outcome of BRCA patients [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the SNHG16/miR-30a/RRM2 axis also accelerates BRCA cell proliferation and invasion, while miR-4500 could downregulate RRM2 and inhibit BRCA cell proliferation, invasion, and migration via suppressing the MAPK signaling pathway [ 38 , 39 ]. Moreover, RRM2 has been included in several bioinformatic-based clinical prognostic models [ 40 , 41 ]. In addition, a single gene bioinformatics study and one clinical pathology research study indicated that RRM2 expression could help in evaluating the outcome of BRCA patients [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…DEPDC1 expression was lower in normal adjacent tissue relative to OSCC tissue. In addition, several studies have found that longer survival in patients with multiple myeloma and hepatocellular carcinoma was significantly correlated with a lower DEPDC1 expression, suggesting that DEPDC1 may be a new diagnostic marker ( 30 , 31 ). According to these reports, increased DEPDC1 in OSCC cancer significantly correlated with shorter patient survival times.…”
Section: Discussionmentioning
confidence: 99%
“…The formula is a linear combination of the gene expression value of each gene and the regression coefficient (β) [ 20 ]. The R-survminer, R-survival, and R-ggrisk packages were used to draw a risk plot [ 21 , 22 ]. The objective of constructing a Cox proportional hazards regression model was to assess the relative contribution of key prognostic genes to patient survival prediction.…”
Section: Methodsmentioning
confidence: 99%